The influence of carbon perception on sustainable behaviors: Tailoring sustainability strategies based on individuals' levels of openness to green technology adoption - Sasichakorn Wongsaichia; Teerapong Pienwisetkaew; Wanwisa Wannapipat; Khwanjira Ponsree; Chavis Ketkaew (Cleaner and Responsible Consumption)
Global concerns over rising carbon emissions emphasize the critical role of individual actions in mitigating climate change. Technology provides a powerful means to support sustainable behavior, offering tools that help individuals monitor, manage, and reduce their carbon footprints effectively. This study extends the value-belief-norm theory to examine how perceived carbon impact influences sustainable behavior, focusing on how openness to green technology adoption (traditionalists versus technology enthusiasts) moderates this relationship. We explore both direct and indirect pathways from perceived carbon impact to sustainable behavior, with environmental awareness and intention to adopt green technology as key mediators. Using multigroup structural equation modeling, data from 542 users of a carbon footprint platform in Thailand were analyzed. Results reveal distinct pathways: traditionalists rely on an indirect route where perceived carbon impact promotes sustainable behavior through enhanced environmental awareness and intention, while technology enthusiasts display a direct link between perceived carbon impact and sustainable behavior. Despite these differences, the overall effect of perceived carbon impact on sustainable behavior remains similar across groups. These findings underscore the need for targeted sustainability interventions. For traditionalists, strategies that build environmental awareness and foster intentions to adopt green technologies are more effective, whereas for technology enthusiasts, emphasizing direct technology-enabled actions can drive significant behavioral change.